1983
DOI: 10.1002/ana.410140506
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of treatment on endocrine function in children with brain tumors

Abstract: Fourteen children with brain tumors received endocrine evaluations at least one year following completion of cranial irradiation. Treatment consisted of operation (13 patients), craniospinal irradiation (6), whole brain irradiation (5), posterior fossa irradiation (3), and chemotherapy (10). Endocrine evaluation included bone age roentgenography and measurement of growth hormone (using sequential arginine and insulin stimulation), thyroxine, thyroid-stimulating hormone, plasma cortisol, testosterone, prolactin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
4

Year Published

1985
1985
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 8 publications
0
23
0
4
Order By: Relevance
“…Pro spective studies revealed that hypothalamic-pituitary function is normal immediately after surgery and before radiotherapy [5,6], The occurrence of GH deficiency as the earliest and often the only endocrine abnormality in children, who have undergone cranial irradiation, sug gests that this axis is the most sensitive to the deleterious effects of irradiation [7], There are no detailed studies of the sequence of pituitary hormone deficit following irra diation in childhood. However, our data [8] in adults irradiated (total dose 3,750-4,250 cGy) for pituitary tumours confirm this Finding with a 100% incidence of GH deficiency at 5 years ( fig.…”
Section: Radiation and Pituitary Functionmentioning
confidence: 99%
“…Pro spective studies revealed that hypothalamic-pituitary function is normal immediately after surgery and before radiotherapy [5,6], The occurrence of GH deficiency as the earliest and often the only endocrine abnormality in children, who have undergone cranial irradiation, sug gests that this axis is the most sensitive to the deleterious effects of irradiation [7], There are no detailed studies of the sequence of pituitary hormone deficit following irra diation in childhood. However, our data [8] in adults irradiated (total dose 3,750-4,250 cGy) for pituitary tumours confirm this Finding with a 100% incidence of GH deficiency at 5 years ( fig.…”
Section: Radiation and Pituitary Functionmentioning
confidence: 99%
“…As the dose of radiation increases, both hypotha lamic and pituitary control of growth hormone regula tion may become affected, as reflected by abnormal in sulin and arginine stimulation tests [60]. Additionally, in children treated before puberty, linear growth will de celerate [61 ]. One prospective study has shown that up to 86% of children tested had abnormalities on growth hormone testing by 1 year [62].…”
Section: Late Effectsmentioning
confidence: 99%
“…However, infants and very young children less than 3 years old with primary central nervous system tumors have a poor prognosis due to the increased likelihood of disseminated disease at diagnosis and the morbidity of whole brain irradiation, among other factors (Duffner et al, 1983;Gajjar et al, 1994;Walter et al, 1999;Mulhern et al, 2004;Laughton et al, 2008). Little is known about the disposition of many anticancer drugs in infants and young children, which often leads to increased risk of morbidity, poor tumor control, and increased risk of late effects.…”
Section: Introductionmentioning
confidence: 99%